The kinetics and mechanism of micelle-vesicle transitions in aqueous solution - Farquhar, K.D.; Misran, M.; Robinson, B.H.; Steytler, D.C.; Morini, P.; Garrett, P.R.; Holzwarth, J.F. (1996)
Bi-chained surfactants, e.g. sodium dialkylbenzenesulphonates, can spontaneously form vesicles when salts (e.g. NaCl) are added to water. Critical vesicle concentrations can be readily determined. The kinetics and mechanism for the breakdown and formation of vesicles will be discussed. A mechanism for assembly/disassembly is proposed. Organic dyes can be encapsulated inside the vesicles and their release rates can be monitored using flow experiments. It is found that the vesicle bilayer provides a rather low energy barrier to the transport of the dye from the vesicle core to the external aqueous medium.